Avian retrovirus integrase-enhanced transgene integration into mammalian cell DNA in vivo - Aqing Yao; Roger Chiu; Ajaykumar Vora; David B. Brown; Duane Grandgenett; Brian R. Davis (BioTechniques, 2003)
Systems for introducing DNA genes-of-interest into mammalian cellular genomes have ranged from the use of different physical techniques to viruses including retroviruses. We have developed a microinjection method for an efficient and permanent integration of a DNA transgene into the cell genome by use of the retrovirus integrase. A 3.0-kb linear DNA fragment containing an internal herpes simplex virus thymdine kinase gene (tk) with flanking avian retrovirus U5 and U3 terminal attachment sites (U5-pgk/tk-U3) recognized by the integrase was constructed. The other donor, a 3.3-kb linear DNA fragment containing the same gene (pgk/tk) flanked by ApaL1 restriction sites not recognized by integrase, was also produced. After assembly of integrase-transgene complexes on ice, the complexes were microinjected into the nucleus of human fibroblast cells (143Btk-) containing a defective thymidine kinase. The number of hypoxanthine/aminopterin/thymidine (HAT)-resistant colonies produced upon microinjection of either naked DNA or the independently assembled integrase-transgene complexes were determined. Our data suggests that enhanced integration of U5-pgk/tk-U3 required the DNA attachment sites and co-delivery of integrase. The data was consistent with a direct role for both of these elements in producing an approximate 4-fold increase in the number of HAT-resistant colonies observed over microinjection of just naked U5-pgk/tk-U3 (P < 0.0001).